The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00127-015-1115-1
|View full text |Cite
|
Sign up to set email alerts
|

An “immigrant paradox” for adolescent externalizing behavior? Evidence from a national sample

Abstract: Purpose Recent decades have witnessed a rise in the number of immigrant children in the United States (US) and concomitant concerns regarding externalizing behaviors such as crime, violence, and drug misuse by immigrant adolescents. The objective of the present study was to systematically compare the prevalence of externalizing behaviors and migration-related factors among immigrant and US-born adolescents in the US. Method Data on 12 to 17 year olds (Weighted N in thousands = 25,057) from the National Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 49 publications
1
49
1
Order By: Relevance
“…If immigrants integrate into the destination country, we would expect to find a convergence toward the majority's health level across immigrant generations or across time spent in the destination country. Although some earlier studies suggested such a pattern (e.g., Harker, ; Montazer & Wheaton, ; Salas‐Wright et al, ), our previous analyses (Mood et al, in press) revealed no or very little convergence in the countries we examined. We have therefore included both the first (born abroad) and second (born in the host country to immigrant parents) generation in our immigrant origin groups, but we controlled for generation in our analyses (which did not alter the results).…”
Section: The Current Studycontrasting
confidence: 60%
See 2 more Smart Citations
“…If immigrants integrate into the destination country, we would expect to find a convergence toward the majority's health level across immigrant generations or across time spent in the destination country. Although some earlier studies suggested such a pattern (e.g., Harker, ; Montazer & Wheaton, ; Salas‐Wright et al, ), our previous analyses (Mood et al, in press) revealed no or very little convergence in the countries we examined. We have therefore included both the first (born abroad) and second (born in the host country to immigrant parents) generation in our immigrant origin groups, but we controlled for generation in our analyses (which did not alter the results).…”
Section: The Current Studycontrasting
confidence: 60%
“…The results on family cohesion and parental warmth or closeness are more mixed: Kao () reported more family closeness among Asian and Latino groups in the United States than among nonimmigrants, but Chao () found no significant differences for Chinese immigrants, and Bankston and Zhou () found less closeness in immigrant families. Salas‐Wright et al () showed that recently arrived immigrant adolescents reported more parental support and less parent–child conflict than those born in the United States.…”
Section: The Family Situation Of Adolescents Of Immigrant Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information, including the variable prompts, response options, and corresponding coding structure, is provided in Table 3. Consistent with previous NSDUH-based studies, the response options for each of these items were dichotomized so as to enhance the interpretability of results (DeLisi, Vaughn, & Salas-Wright, 2015;Salas-Wright, Vaughn, Schwartz, & Córdova, 2015). …”
Section: Handgun Carrying Youth In Usamentioning
confidence: 99%
“…Age, sex [0 (male), 1 (female)], birth country [0 (born in Australia), 1 (born overseas)], and baseline truancy (‘How many days did you have off school last year without your parents’ permission?’ [five‐point scale from 0 (zero days) to 10 (10 or more days)] and grades (‘What grades do you usually get in school?’ [six‐point scale from 49% and below to 90–100%)] were controlled for given their influence on adolescent drinking . Consent type [0 (active) and 1 (passive)] was included to control for the over‐representation of private school students.…”
Section: Methodsmentioning
confidence: 99%